Outcomes of Nulliparous Women with Spontaneous Labor Onset Admitted to Hospitals in Pre‐active versus Active Labor. (8th October 2014) - Neal, Jeremy L.
Abstract : Purpose: The aims of this study were to estimate the percentage of low‐risk, nulliparous women with spontaneous labor onset who are admitted to labor units prior to active labor and to evaluate the effects of the timing of admission (ie, pre‐active versus active labor) on labor interventions and mode of birth. Research Questions: What percentage of low‐risk, nulliparous women are admitted to labor units prior to active labor onset? Are women admitted to hospitals in pre‐active labor more prone to exogenous oxytocin augmentation, amniotomy, and cesarean birth? Significance: The timing of when a woman is admitted to the hospital for labor care following spontaneous contraction onset may be among the most important decisions that labor attendants make as it may influence care patterns and birth outcomes. Methods: Obstetric data from low‐risk, nulliparous women with spontaneous labor onset (N = 216) were merged from 2 prospective studies conducted at 3 large Midwestern hospitals. Women dilating less than 0.5 cm per hour, on average, for the first 4 hours post‐admission were classified in the pre‐active labor group while those dilating 0.5 cm or greater per hour were classified in the active labor group. Baseline characteristics, labor interventions, and outcomes were compared between groups using Fisher's exact and Mann‐Whitney U tests, as appropriate. Likelihoods for oxytocin augmentation, amniotomy, and cesarean were assessed by logistic regression. Results: Of the sample of 216 low‐risk, nulliparous women, 114 (52.8%) were admitted in pre‐active labor, and 102 (47.2%) were admitted in active labor. Women who were admitted in pre‐active labor were more likely to undergo oxytocin augmentation (84.2% and 45.1%, respectively; odds ratio [OR], 6.5; 95% confidence interval [CI], 3.43–12.27) but not amniotomy (55.3% and 61.8%, respectively; OR, 0.8; 95% CI, 0.44–1.32) when compared to women admitted in active labor. The likelihood of cesarean was higher for women admitted before active labor onset (15.8% and 6.9%, respectively; OR, 2.6; 95% CI, 1.02–6.37). Discussion: Many low‐risk, nulliparous women with regular, spontaneous uterine contractions are admitted to labor units before active labor onset, which increases their likelihood of receiving oxytocin and giving birth via cesarean. An evidence‐based, standardized approach for labor admission decision making is recommended to decrease inadvertent admissions of women in pre‐active labor. When active labor cannot be diagnosed with relative certainty, observation before admission to the birthing unit is warranted.